Efficacy and safety of stem cell mobilization with etoposide +cytarabine plus G-CSF in poor mobilizers with relapsed or refractory lymphoma - Zhu, Zhijuan; Li, Xiaofan; Yuan, Xiaohong; Chen, Xianling; Lin, Ting; Guo, Xiangli; Li, Nainong (Frontiers in Immunology, 2024)
Background: Autologous stem cell transplantation (ASCT) is a potentially curative strategy for relapse or refractory(r/r) aggressive lymphoma. However, a proportion of lymphoma patients who are at high risk of mobilization failure fail to mobilize stem cells and cannot proceed to ASCT. The aim of this study is to explore the efficacy and safety of Etoposide combined with Cytarabine (EA) plus G-CSF mobilization in poor mobilizers (PMs) with r/r aggressive lymphoma.Methods: This retrospective study analyzed the outcomes of chemo-mobilization based on EA (Etoposide 0.1 g/m2, qd d1 3; AraC 0.5 g/m2, q12h d1 3) in 98 patients with r/r aggressive lymphoma. Of these, 39 patients met the criteria for predicted PMs as proposed by the Gruppo Italiano Trapianto di Midollo Osseo working group.Results: Of the 39 PMs, 38(97.4%) patents harvested adequate mobilization (≥2×10 6 CD34+ cells/kg), while 31(79.5%) patients achieved optimal mobilization (≥5×10 6 CD34+ cells/kg). Overall, the mean number of CD34+ cells/kg collected was 17.99(range: 1.08 83.07) ×10 6 with an average of 1.4 apheresis sessions, and the number was 15.86(range: 0.37 83.07) ×10 6 for the first apheresis, respectively. A single apheresis procedure was sufficient to reach the target yield of adequate mobilization in 35(89.7%) PMs, while 76.9% of PMs achieved optimal collection within two apheresis sessions. We observed acceptable hematological toxicity and antibiotic usage exposure in 26 patients with a mean duration of 3.6 days. No grade 4 infection or mobilization-related mortality was recorded. Most patients underwent ASCT and achieved successful hematopoietic recovery with prompt engraftment duration, except for one NK/T-cell lymphoma patient who succumbed to severe septicemia after receiving conditioning chemotherapy.Conclusion：Our findings indicate that EA plus G-CSF is an effective and tolerable CD34+ stem cell mobilization strategy for patients with r/r lymphoma, including those predicted to be PMs. This regimen could be an option for patients with r/r lymphoma, particularly those undergoing mobilization for salvage ASCT therapy.